Diffuse Skin Reaction in Patient with Hepatitis B, Treated with Two Different Formulations of Pegylated Interferon - Piotr Milkiewicz; Colina Yim; Isabelle Pache; J Heathcote (Canadian Journal of Gastroenterology)
Diffuse skin reactions, commonly leading to discontinuation of the treatment, have been reported in patients with hepatitis C treated with interferon. They were not as yet described in patients treated with a newer formulation of interferon, namely, pegylated interferon (PegINF). A 37-year-old male patient with viral hepatitis B developed a diffuse urticarial skin reaction during treatment with two different forms of PegINF. Despite the skin reaction, the treatment was continued, and the patient responded very well to topical steroids and antihistamines. The present report suggests that despite the severity of reaction, withdrawal of PegINF may not always be required because this particular skin reaction responded well to symptomatic treatment. This is important, because discontinuation of PegINF may decrease the chance of achieving a sustained virological response in patients with viral hepatitis.